Evaluating Seismic Response of Plan Irregular Buildings Using Combination of Lead Rubber Bearing Isolator and Friction Pendulum System - Mahmoud Reza Shiravand (Iranian Society of Structrual Engineering (ISSE), 2021)
Recently, base isolation techniques are applied as a resisting system to protect the structures from seismic and dynamic loadings. Due to their importance, in this paper, an optimum arrangement of lead rubber bearing (LRB) and friction pendulum system (FPS) is investigated in irregular buildings and its performance is compared with a regular case. For this purpose, 3 types of irregularities have been adopted. Accordingly, 3, 7 and 10 story buildings have been performed and 12 possible combination have been applied for the isolators in each model. Afterwards, the numerical models have been analyzed using nonlinear time-history analysis and direct integration method and applying 7 earthquake records along the longitudinal and transverse directions of the building. The obtained results of the numerical study show that the application of FPS and LRB isolators in outer and inner columns respectively, led to a better performance compared to the other arrangements by reduction of the inter-story drifts as well as base shear and enhancement of the energy dissipation which is due to the characteristics of FPS isolators in balancing the applied forces with the building’s mass and prevention of torsion occurrence in irregular structures. Unlike the irregular buildings, application of FPS and LRB isolators in inner and outer columns, result in a better performance by reducing the story drifts in regular structures.